(untitled) (Agora for Physical Education and Sport, 2021)
Leisure, physical activity and body practices constitute a problematic that can be analyzed from at least two perspectives: i) a critical approach to classic theories which underlines the present work; ii) the analysis of the “almost minor” concepts and problems against the framework imposed by a pandemic which, as such, spans globalization and works in favor of a global government of the population. In this context, the body becomes the preferential and clear crux of the matter, from where power is wielded and danger is exteriorized at the same time. This is a hermeneutic line of study that allows the tracking and revision of classic concepts, now being challenged by this new historical event. The hypothesis of this work is that the body issue and the body practices are at the organizing core of the isolated life style and, at the same time, the place from where the distinguishing mechanisms operate.